Estudo da resposta espectral de alvos urbanos com espectroscopia de reflectância e imagens de alta resolução espacial - Durán, Gloria Yamileth Bolívar (2014)
Urban areas are composed with diverse set of materials arranged in a complex way by man for its survival. Remote sensing is the tool with potential for obtain spectral data of urban materials and their conditions. This study presents the spectral characterization behavior of urban targets in part of Santa Maria city e showed the spectral discrimination capability of urban targets with GeoEye-1 and HRG-1/SPOT 5 sensors. A spectral library of urban materials was created to analysis with field spectral measurements and specification of reference spectrum in the images. Qualitative and quantitative analysis was applied to identify and describe urban targets characteristics. Finally the capability of spectral identification of urban materials was evaluated, using Spectral Angle Mapper (SAM) technique and spectral resampling technique with the spectral response function of GeoEye-1 and HRG- 1/SPOT 5 sensors for comparing reference spectrum chosen. The results showed that: (1) In some cases the distinction between targets was for only small differences in magnitude. (2) The field measurements were performed with a FieldSpec® HandHeld 2 spectroradiometer, which use VIS and partially NIR spectral range, a limiting factor in the analysis of targets with distinctive features in the SWIR. (3) Materials with some colorful cover showed spectral responses correspond to the ink, but not on the type of material. (4) Materials as red ceramic tiles, dirt roads and clay courts preserve the reflectance properties of the base material, (5) The manufactured targets with concrete, asbestos tiles, shingle tile, asphalt, gravel, cobblestone pavements, steel and zinc tile, always lacking some paint cover on the surface, exhibit no spectral features defined variations that cause confusion at the classification, (6) The weathering actions on urban targets affect the spectral response of the materials. (7) The resampling of spectral curves showed the spectral shape of images and field measurements was preserved in most cases even though the absolute amplitude reflectance has variations. (8) The SAM technique with some limitations allowed the identification of urban targets with greater than 50% accuracy. The GeoEye-1 image enables an approach to discriminate some intra-urban patterns, an aspect that the HRG-1/SPOT 5 image does not.